Australian vegetated coastal ecosystems as global hotspots for climate change mitigation - Oscar Serrano (Nature Portfolio, 2019)
Policies aiming to preserve vegetated coastal ecosystems (VCE) to mitigate greenhouse gas emissions require national assessments of blue carbon resources. Here the authors assessed organic carbon storage in VCE across Australian and the potential annual CO2 emission benefits of VCE conservation and find that Australia contributes substantially the carbon stored in VCE globally.